Study of the efficacy of the Hero program: cross-national evidence - Mesurado, Belén (2020)
The present study focuses on an analysis of the efficacy of the online intervention program called “Hero” for promoting prosociality and other socioemotional variables related to prosocial behavior, such as empathy, positive emotions, and forgiveness, in two Latin American countries: Argentina and Uruguay. The final Argentinean sample consisted of 579 adolescents (experimental group = 319 and control group = 260), and the Uruguayan sample consisted of 330 adolescents (experimental group = 140 and control group = 169), aged 12 to 15 years old. The ‘Hero’ program provided evidence of efficacy for the promotion of prosociality, empathy, positive emotions, and attitudes of forgiveness. It impacted each of the dimensions comprising these variables differently depending on the country where it was applied. We discuss the differences found in each country.